Association of a Novel Mutation in the Plasmodium falciparum Chloroquine Resistance Transporter With Decreased Piperaquine Sensitivity. (17th July 2017) - Agrawal, Sonia; Moser, Kara A; Morton, Lindsay; Cummings, Michael P; Parihar, Ankita; Dwivedi, Ankit; Shetty, Amol C; Drabek, Elliott F; Jacob, Christopher G; Henrich, Philipp P; Parobek, Christian M; Jongsakul, Krisada; et al.
Summary: The F145I mutation within the Plasmodium falciparum chloroquine resistance transporter is associated with decreased ex vivo piperaquine susceptibility and dihydroartemisinin-piperaqiune treatment failure. Abstract: Background: Amplified copy number in the plasmepsin II / III genes within Plasmodium falciparum has been associated with decreased sensitivity to piperaquine. To examine this association and test whether additional loci might also contribute, we performed a genome-wide association study of ex vivo P. falciparum susceptibility to piperaquine. Methods: Plasmodium falciparum DNA from 183 samples collected primarily from Cambodia was genotyped at 33716 genome-wide single nucleotide polymorphisms (SNPs). Linear mixed models and random forests were used to estimate associations between parasite genotypes and piperaquine susceptibility. Candidate polymorphisms were evaluated for their association with dihydroartemisinin-piperaquine treatment outcomes in an independent dataset. Results: Single nucleotide polymorphisms on multiple chromosomes were associated with piperaquine 90% inhibitory concentrations (IC90 ) in a genome-wide analysis. Fine-mapping of genomic regions implicated in genome-wide analyses identified multiple SNPs in linkage disequilibrium with each other that were significantly associated with piperaquine IC90, including a novel mutation within the gene encoding the P. falciparum chloroquine resistance transporter, PfCRT. This mutation (F145I) was associated with dihydroartemisinin-piperaquine treatment failure after adjusting for the presence of amplified plasmepsin II/III, which was also associated with decreased piperaquine sensitivity. Conclusions: Our data suggest that, in addition to plasmepsin II/III copy number, other loci, including pfcrt, may also be involved in piperaquine resistance.